Surgeries and surgical site infection in India: A analysis of Health Management Information System 2019-2020 - SR Vatavati; MS Kampli (Journal of Surgery and Surgical Research - Peertechz Publications, 2020)
Surgical site infection is defined as an infection occurs within 30 days after the operation if no implant is left in place or within one year if implant is in place and the infection appears to be related to the operation and infection involves deep soft tissue (e.g. fascia, muscle) of the incision and/or the infection appears to be related to the operation and infection involves any part of the anatomy other than the incision that was opened or manipulated during an operation (e.g. organs and spaces) [1].